Contribution of multivariate analysis for evaluation indicators of graduate programs: an analysis in Mathematics (2007-2009) - Gutierres Castanha, Renata Cristina [UNESP]; Cabrini Gracio, Maria Claudia [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2015)
The aim of this study is to analyze the relationship between the quantitative indicators used by CAPES and the final grade of each graduate program through the application of multivariate statistical procedures, in order to contribute to a better understanding of the Brazilian graduate program evaluation system. We evaluated all 26 graduate programs in the area of Mathematics during the 2007-2009 triennium through multivariate methods according to the following indicators: total number of theses and dissertations defended and average of published articles per permanent professor, according to Qualis stratification. It was observed that, in all cluster analyses, graduate programs with grade 3 were always gathered in one single group, while the ones with other grades were gradually separated with the insertion of more analysis of indicators. In addition, the more indicators were included in the analysis, the more refined and close to the grades attributed by CAPES were the results.
Keywords: Bibliometric indicators; Evaluation of graduate programs; Graduate courses in Mathematics